Effect of Some Performance Indicators of Mathematics in the Nalerigu Senior High School - Salifu, Hussein; Nyamekye, Gabriel; Issahaku, Adam (European Scientific Journal, ESJ, 2017)
This study employed the multivariate analysis of variance (MANOVA) procedure to examine the influence of students’ sex, age and course of study (department) on mathematics performance in Nalerigu Senior High School of the East Mampurisi district in the Northern of Ghana. The results showed that male students perform better on the average for all the mathematics performance indicators (understanding, knowledge and perception). The MANOVA analysis revealed that students performance in mathematics do not differ across sex (gender) and age group. The results however showed that there was significant difference in performance of mathematics across course of study (department). However, the univariate analysis of variance (ANOVA) results revealed that there was no sex difference in understanding and knowledge of mathematics while significant differences exist in perception of mathematics among male and female students. Further, the study revealed a significant difference in students understanding and knowledge in mathematics and no bias in perception of mathematics among students age. The study therefore recommended that, the Ministry of Education, school managements and other stakeholders such as Non Governmental Organizations should sensitize students to discard beliefs and practices that prohibit effective participation of female students which result to poor performance in mathematics.